Proposal of nutrient removal technologies for urban wastewater treatment in the Marmara Sea basin: A strategy for mucilage prevention. - Insel, Güçlü; Ozyildiz, Goksin; Cokgor, Emine; Gurel, Melike; Zengin, Gulsum Emel; Guven, Didem; Erturk, Ali; Ekdal, Alpaslan (Environmental Management, 2025)
There has been mucilage problem in the Marmara Sea, mainly caused by nutrient loads from point and diffuse sources. Total nitrogen from point sources accounts for 74% of the nutrient load, while total phosphorus contributes 22%. Preventing nitrogen loads from urban wastewater is particularly important for the Marmara Sea. Therefore, achieving discharge limits is largely related to the current choices in processes and technologies. More than half of the existing advanced biological wastewater treatment plants use the anaerobic-anoxic-oxic (A2O) process configuration. Due to stringent limitations on nitrogen and phosphorus discharges enforced by new EU directive, it is necessary to revise the existing wastewater treatment plants and apply different process configurations/technologies for newly planned treatment plants. In this study, among the applicable technologies, A2O and Bardenpho processes were evaluated with simulation studies in comparison to novel hybrid Biofilm-Contact Denitrification process. For this purpose, representative wastewater characteristics and reference process kinetics were determined by evaluating the existing seven large scale wastewater treatment plants in the Marmara Region. SUMO© process simulation results showed that Bardenpho and Biofilm-Contact Denitrification process complied with the new stringent EU discharge limits.